Kontribusi Fenomenologi Post-Subjek pada Metodologi Filosofis dan Teologis - Tedjoworo, Hadrianus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2018)
Givenness is probably an odd term in methodology, but not in phenomenology. The long history of subjectivism in philosophy faces confrontations from Derrida's deconstruction. This history also results in a sort of mutual exclusion between philosophy and theology. The concept of the subject becomes a problem for both, but frequently it is safeguarded for the sake of a more universal 'objectivity'. The phenomenological tendency towards phenomenon, more than towards the experiencing subject and more than anything regarded as object, provokes some philosophical focus on the emancipation of the phenomena. Marion pushes phenomenology to its limits, to the extent that he is suspected of undermining the role of the subject in contemporary philosophical discourse. He reacts to Derrida's deconstruction, which was also criticised for not offering a way out of the labyrinth from the collapse of traditional thoughts. Marion is quite consistent with his phenomenology, namely in offering a way out for the subject to be a witness, and reminds that philosophy should be more appreciative of phenomena. The term saturated phenomenon represents his philosophical thinking that can be regarded as a methodological approach to respect, and not to dominate, reality. Being a witness is not the same as playing a critic on reality. This could be a useful stance for philosophers as well as theologians in the presence of the phenomena they cannot master, namely, the given phenomena.